2013
DOI: 10.1519/jsc.0b013e31827f4dbe
|View full text |Cite
|
Sign up to set email alerts
|

Which Skills and Factors Better Predict Winning and Losing in High-Level Men's Volleyball?

Abstract: The aim of this study was to determine which skills and factors better predicted the outcomes of regular season volleyball matches in the Spanish "Superliga" and were significant for obtaining positive results in the game. The study sample consisted of 125 matches played during the 2010-11 Spanish men's first division volleyball championship. Matches were played by 12 teams composed of 148 players from 17 different nations from October 2010 to March 2011. The variables analyzed were the result of the game, tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
55
4
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 12 publications
7
55
4
10
Order By: Relevance
“…Specifically, it should be noted that blocker role and its relation at game, as it is widely studied and collected in literature (Peña, Rodríguez-Guerra, Buscà, & Serra, 2013). The digger role, as well as the defensive JOSE MANUEL JIMENEZ-OLMEDO, ALFONSO PENICHET-TOMAS -------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it should be noted that blocker role and its relation at game, as it is widely studied and collected in literature (Peña, Rodríguez-Guerra, Buscà, & Serra, 2013). The digger role, as well as the defensive JOSE MANUEL JIMENEZ-OLMEDO, ALFONSO PENICHET-TOMAS -------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is essential to investigate the relationship involving performance indicators of the game, and predictive studies are predominantly related to the relationship between sports skills and success in the game, player position, game phase 3 and place of attack 4 . Volleyball surveys have sought to understand the game in terms of the final result of the game [5][6] , the position of the team at the end of the competition [7][8] and type of game [9][10] , showing that high performance levels in serve 5 , attack 11 , and block 7 can predict success in the game. In this context, studies have shown that attack was the fundamentals that most influenced the conquest of scores and the final result of the game 12 , requiring that the offensive construction, when there are ideal conditions of distributions, occurs with four attackers 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, studies have shown that attack was the fundamentals that most influenced the conquest of scores and the final result of the game 12 , requiring that the offensive construction, when there are ideal conditions of distributions, occurs with four attackers 13 . However, researches were mostly focused on the general understanding of the game practiced, specifically the effectiveness of actions 11,14 , disregarding the situational constraints imposed on the different situational scenarios. In addition, it was observed that the analysis of the game mostly occurs from attacks carried out from positions 2, 3 and 4, since these positions are the most requested by the setter 4 .…”
Section: Introductionmentioning
confidence: 99%
“…As pesquisas em voleibol buscaram a compreensão do jogo em função do resultado final da partida (7,49) , da classificação da equipa no final da competição (32,34) e do tipo de jogo praticado (18,19) , mostrando que níveis elevados de desempenho no saque (7) , ataque (46) e bloqueio (32) podem prever o sucesso na partida. Dentre os fundamentos, a literatura vem evidenciando o ataque como a ação que mais influencia na conquista dos pontos e no resultado final da partida (13,33,46) , sendo necessário que a construção ofensiva, quando há condições ideais de distribuições, ocorra com quatro atacantes (15) .…”
Section: Introductionunclassified
“…Dentre os fundamentos, a literatura vem evidenciando o ataque como a ação que mais influencia na conquista dos pontos e no resultado final da partida (13,33,46) , sendo necessário que a construção ofensiva, quando há condições ideais de distribuições, ocorra com quatro atacantes (15) . Entretanto, uma vez que a distribuição do levantador se mostra dependente da qualidade da receção (21) , da disponibilidade dos atacantes (3) e da disposição dos bloqueadores (7) , observa-se a tendência de maior solicitação dos atacantes das extremidades da rede, principalmente dos atacantes da zona 4 (15,42,44) , tal como atestado pelos dados estatísticos da Superliga Brasileira de 2014/ 2015, onde 34% dos ataques foram realizados da zona 4.27% da zona 2.24% da zona 3, 10% da zona 1 e 5% da zona 6 (12) .…”
Section: Introductionunclassified